Peningkatan Pemahaman Konsep Perubahan Materi Melalui Perbaikan Bahan Ajar - Wibowo, Agus Mukti (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2013)
Student understanding of the concept of Natural Sciences, especiallyÂ â€œmaterial and its changesâ€ are inflenced by the students understandingÂ of the previous material on the â€œvarious substances and natureâ€. TheÂ development of learning sources about â€œmaterial and its changesâ€ canimprove students understanding of the concept, in this case is studentsÂ of college, if (1) making the media of teaching based on the basic conceptsÂ about material that will be learned by students and that concepts arrangedsystematically or sequentially concepts, for example from simple to complexÂ concept or from the lower to the higher concept, (2) the examples thatÂ given to the students close to the students experiences, beginning from aÂ simple example.Keywords: â€œMaterial and Its changesâ€, Remedical of LearningSources.